PENGARUH PROBLEM BASED LEARNING DAN SAINS TEKNOLOGI MASYARAKAT TERHADAP MOTIVASI BELAJAR - Awalina Barokah (JURNAL INOVATIF ILMU PENDIDIKAN, 2021)
This study aims to reveal : (1) the effect of PBL on the motivation to learn; (2) the effect of STM on the motivation to learn; (3) differences on the motivation to learn between the group taught using PBL model and that taught using STM. This study was a quasi experiment with the nonequivalent comparison-group design. The data analysis used T-test and Univariate Analysis of Variance at the significance level of 5%. The results are as follows: (1) PBL improved positively and significantly on the motivation to learn; (2) STM improved positively and significantly on the motivation to learn; (3) there is a significant and positive difference on the motivation to learn between the group taught using PBL model and that taught using STM modelKeywords: Problem-Based Learning, Science Technology and Society, Motivation to LearnDOI: http://dx.doi.org/10.23960/jiip.v3i1.22277